THE INHIBITORY ACTIVITY OF KELAKAI LEAF EXTRACT AGAINST THE GROWTH OF Porphyromonas gingivalis ATCC® 33277™ - Destri Khusnul Khotimah; I Wayan Arya Krishnawan Firdaus; Maharani Laillyza Apriasari (Dentino : Jurnal Kedokteran Gigi, 2020)
ABSTRACTBackground: Chronic periodontitis is an infectious disease that causes damage on periodontal ligament and alveolar bone. The severity of periodontitis is caused by several types of bacterial species which one of them is Porphyromonas gingivalis bacteria with a prevalence of 85% in oral cavity. The extract of kelakai leaf contained antibacterial in the form of flavonoid, alkaloid, tannin, and steroid. Flavonoid consists of some chemical compounds which is one of them is quercetin. The level of quercetin in kelakai leaf is 503.56 mgQE/g. From some secondary metabolites, kelakai leaf has inhibitory power toward gram negative bacterial, Porphyromonas gingivalis. Objective: This research was intended to know the activity of inhibitory power of kelakai leaf toward Porphyromonas gingivalis bacteria. Method: This research was an experimental research consisted of 5 experimental groups that were group of kelakai leaf extract on the concentrations of 100 mh/ml, 75 mg/ml, 50mg/ml, and 25 mg/ml and the control group (0.2% chlorhexidine). Each treatment was done in 4 repetitions. The test of inhibitory power used diffusion method by measuring the inhibitory zone around the growth of Porphyromonas gingivalis on Mueller Hinton Agar media. The data were analyzed by using One Way Anova 95% and then continued with LSD. Results: Based on the LSD test, it was known that the extract of Kelakai leaf had inhibitor power activity toward Porphyromonas gingivalis. The highest inhibitory zone was on the concentration of 100 mg/ml with inhibitory zone of 14.61 mm. Conclusion: The extract of kelakai leaf had inhibitory power activity toward Porphyromonas gingivalis bacteria in vitro. Keywords: 0.2% chlorhexidine, Diffusion method, Inhibitory power, Stenochlaena palustris extract, Porphyromonas gingivalis.